Cannabinoids in Neurology - Position paper from Scientific Departments from Brazilian Academy of Neurology - BRUCKI, Sonia Maria Dozzi; ADONI, Tarso; ALMEIDA, Carlos Mauricio Oliveira; ANDRADE, Daniel Ciampi de; ANGHINAH, Renato; BARBOSA, Luciana Mendonça; BAZAN, Rodrigo; CARVALHO, Alzira Alves de Siqueira; CARVALHO, William; CHRISTO, Paulo Pereira; COLETTA, Marcus Della; CONFORTO, Adriana Bastos; CORREA-NETO, Ylmar; ENGELHARDT, Eliasz; FRANÇA, Marcondes Cavalcante, JUNIOR; FRANCO, Clelia; VON GLEHN, Felipe; GOMES, Helio Rodrigues; HOULY, Caroline Gomes de Barros; KAUP, Alexandre Ottoni; KOWACS, Fernando; KANASHIRO, Aline; LOPES, Victor Gonçalves; MAIA, Débora; MANREZA, Maria; MARTINEZ, Alberto Rolim Muro; MARTINEZ, Sandra Cristina Gonçalves; NADER, Saulo Nardy; NEVES, Luciana de Oliveira; OKAMOTO, Ivan Hideyo; OLIVEIRA, Rogério Adas Ayres de; PEIXOTO, Fabiano de Melo; PEREIRA, Cristiana Borges; SABA, Roberta Arb; SAMPAIO, Leticia Pereira de Brito; SCHILLING, Lucas Porcello; SILVA, Marcus Tulius Teixeira; SILVA, Emanuelle Roberta; SMID, Jerusa; SOARES, Cristiane Nascimento; SOBREIRA-NETO, Manoel; SOUSA, Nise Alessandra de Carvalho; SOUZA, Leonardo Cruz de; TEIVE, Hélio Afonso Ghizoni; TERRA, Vera Cristina; VALE, Matheus; VIEIRA, Vitor Mendes Grise; ZANOTELI, Edmar; PRADO, Gilmar (Arquivos de Neuro-Psiquiatria, 2021)
Cannabinoids comprehend endocannabinoids, phytocannabinoids, and synthetic cannabinoids, with actions both in the central and peripherical nervous systems. A considerable amount of publications have been made in recent years, although cannabis has been known for over a thousand years. Scientific Departments from the Brazilian Academy of Neurology described evidence for medical use in their areas. Literature is constantly changing, and possible new evidence can emerge in the next days or months. Prescription of these substances must be discussed with patients and their families, with knowledge about adverse events and their efficacy.
Keywords: Cannabis; Cannabinoids; Neurology; Cannabidiol